2021
DOI: 10.1007/s12528-021-09289-9
|View full text |Cite
|
Sign up to set email alerts
|

Improve teaching with modalities and collaborative groups in an LMS: an analysis of monitoring using visualisation techniques

Abstract: Monitoring students in Learning Management Systems (LMS) throughout the teaching–learning process has been shown to be a very effective technique for detecting students at risk. Likewise, the teaching style in the LMS conditions, the type of student behaviours on the platform and the learning outcomes. The main objective of this study was to test the effectiveness of three teaching modalities (all using Online Project-based Learning -OPBL- and Flipped Classroom experiences and differing in the use of virtual l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 61 publications
(117 reference statements)
2
20
0
1
Order By: Relevance
“…This finding suggests that there are variables such as learning style that may be conditioning a greater or lesser effectiveness of gamification techniques on learning outcomes. As other studies have already indicated [6,8], it is very difficult to isolate the effects of gamification from those of other factors. However, it seems that the use of these techniques increases the interaction of students in the LMS [2].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This finding suggests that there are variables such as learning style that may be conditioning a greater or lesser effectiveness of gamification techniques on learning outcomes. As other studies have already indicated [6,8], it is very difficult to isolate the effects of gamification from those of other factors. However, it seems that the use of these techniques increases the interaction of students in the LMS [2].…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, no significant differences were found in students satisfaction with teaching depending on the use or non-use of DGBL. One possible explanation is that in all groups, the OPBL methodology was also applied, and this in itself generates indicators of satisfaction [7,8]. In this sense, as previously indicated, the results of this work support those found in other studies that indicate the difficulty of discriminating the unique effects of the use of gamification [6][7][8]23], since both methodological resources, DGBL and OPBL, facilitate the construction of meaningful learning, enhance the use of SRL and increase students satisfaction [3,5,[12][13][14]18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Distant learning and BL has been widely implemented in medical and pharmaceutical education over the last few years with teachinglearning process being increasingly carried out in online or BL environments, reducing the use of the traditional face-to-face interactions [10]. This situation has increased with the crisis due to COVID-19, and these days a high percentage of teaching is done through so called Learning Management Systems (LMSs) [11]. Now LMSs produce a significant impact on the educational process worldwide as software systems that combine different tools used to "systematically deliver content online and facilitate the learning experience around that content" [12,13].…”
Section: Introduction 11 Research Problemmentioning
confidence: 99%
“…However, in order to facilitate effective learning in students, these technological tools must be implemented with appropriate pedagogical designs [4,5]. Consequently, university education today faces many challenges, one of which is the integration of technological resources in LMS to improve teaching [6]. Among these methods is the facilitation of self-regulated learning (SRL) through the use of advanced learning technologies (ALTs) in LMS.…”
Section: Introductionmentioning
confidence: 99%